Training Activities and Injuries in English Youth Academy and Schools Rugby Union. (February 2015) - Palmer-Green, Deborah S.; Stokes, Keith A.; Fuller, Colin W.; England, Michael; Kemp, Simon P.T.; Trewartha, Grant
Background: All rugby training activities carry an injury risk, but in the training environment these injury risks should be more controllable than during matches. Purpose: To (1) describe the incidence, severity, anatomic location, and type of youth rugby training injuries; (2) determine the injury events and type of training activities associated with injuries; and (3) compare 2 levels of play (professional academy vs school) within English youth rugby union. Study Design: Cohort study; Level of evidence, 2. Methods: A 2-season (2006-2007 and 2007-2008) study recorded exposure to training activities and time-loss injuries in male youth rugby union players (age range, 16-18 years) from 12 English Premiership academies (250 player-seasons) and 7 schools (222 player-seasons). Players from the Premiership academies, associated with the top-level professional clubs in England, represented the elite level of youth rugby; the school players were from established rugby-playing schools but were overall considered at a lower level of play. Results: There was a trend for training injury incidence to be lower for the academy group (1.4/1000 player-hours; 95% CI, 1.0-1.7) compared with the school group (2.1/1000 player-hours; 95% CI, 1.4-2.9) ( P = .06). Injuries to the ankle/heel and thigh were most common in academy players and injuries to the lumbar spine and ankle/heel region most common in school players. The training activities responsible for injury differed between the 2 groups: technical skills (scrummaging) for school players and contact skills (defense and ruck/maul drills) for academy players. Conclusion: For injury risk management in youth rugby, coaches of school players should focus on the development of the correct technique during practice of technical skills such as scrummaging, weight training, and skills training, and coaches of academy players should consider the extent to which contact drills are necessary during training.